A copper alloy strip and its preparation method and application
By adding specific elements combinations and process processing to the copper alloy, the second strengthening phase is formed, which solves the problem of insufficient performance of existing copper alloy materials, and realizes high-strength and excellent conductive properties of copper alloy strips, suitable for 5G electrical components connectors and shrapnel.
Patent Information
- Application Number
- CN202310880899.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-07-18
AI Technical Summary
Existing copper alloy materials are difficult to meet the requirements of ultra-high strength, excellent conductivity and high-temperature softening performance, especially in the connectors and shrapnel applications of 5G electrical components.
The copper alloy ratio of Ni: 22-24 wt%, Al: 4-5 wt%, Sn: 6-7 wt%, Ce: 0.05-0.1 wt%, to form the second reinforced phase Ni3Al and Ni3Sn, and is quickly hot rolled by high temperature. , solid solution annealing and aging heat treatment process, control the grain size within 2μm, and ensure the filling and analysis of the second phase reinforced phase and optimize the distribution.
It realizes the ultra-high strength, excellent conductivity and high-temperature softening properties of copper alloy strips, with tensile strength exceeding 1310MPa and a conductivity of 18% IACS. It is suitable for connectors and shrapnel of 5G electrical components.
Smart Images

Figure BDA0004344543020000141 
Figure BDA0004344543020000151
Abstract
Description
Technical Field
[0001] The invention belongs to the field of copper alloys, and in particular relates to a copper alloy strip and a preparation method and application thereof. Background Art
[0002] With the rapid development of 5G communications around the world, the connectors and shrapnel of some electrical components in electronic appliances are also developing towards ultra-thinness and miniaturization, while requiring large current transmission and excellent heat dissipation performance. Therefore, the copper strips used to produce these connectors and shrapnel have requirements for ultra-high strength, excellent elasticity, good stress relaxation resistance and good conductivity.
[0003] At present, a micro-control electronic appliance requires the use of copper alloy, with a tensile strength of more than 1200MPa, a hardness of more than 350HV, a conductivity of more than 15%IACS, an elastic modulus of more than 135GPa, and a high-temperature softening resistance of more than 95% (i.e., the hardness of the material at 450℃ for 2h and the percentage of the original hardness of the material). In the early stage, beryllium copper C17200 was used to produce this product, but beryllium oxide (BeO) will be formed during the production process of beryllium copper and in the subsequent processing such as smelting, casting, heat treatment, welding and cutting machine processing. Beryllium oxide is a type of carcinogen, so the industry has proposed a demand to replace beryllium copper C17200.
[0004] Currently in the copper alloy production industry, the performance of beryllium copper C17200 is closest to titanium copper C19920, whose strength can reach above 1200MPa, but its conductivity is lower than 15%IACS. The strength of other existing copper alloys is difficult to reach the requirement of above 1200MPa.
[0005] The patent document with publication number CN114672693A discloses a copper alloy and a preparation method thereof, wherein the mass percentage composition of the copper alloy is Fe: 0.02-0.25wt%, P: 0.01-0.4wt%, Ni: 2.6-3.5wt%, Si: 0.55-0.7wt%, Mg: 0.05-0.15wt%, Zn: 0.01-0.05wt%, rare earth: 0.05-0.1wt%, and the balance is Cu and inevitable impurities. The invention adds Ni, Si, Fe, P, Mg, Zn and rare earth to the copper matrix, and controls the addition amount of each element, so as to achieve the hardness of the copper alloy ≥ 260HV and the conductivity ≥ 45%IACS, but the strength of the alloy cannot meet the requirement of more than 1200MPa.
[0006] Patent document with publication number CN116136005A discloses a copper alloy strip and its preparation method and application, wherein the copper alloy strip comprises the following components in mass percentage: Cu 87-88wt%, Ag 0.1-0.15wt%, Ni 0.4-0.6wt%, P 0.02-0.03wt%, the balance Zn, and inevitable trace impurities. The copper alloy strip of the invention has high strength, good resistance to high temperature softening, and excellent welding performance, but its strength is difficult to reach the requirement of more than 1200MPa.
[0007] Therefore, in view of the above-mentioned deficiencies in the prior art, it is of great significance to find a suitable copper alloy raw material and processing technology to prepare a copper alloy strip with ultra-high strength, ultra-high elasticity, excellent high temperature softening resistance and good electrical conductivity. Summary of the invention
[0008] In view of the above-mentioned deficiencies in the prior art, the present invention provides a copper alloy strip having ultra-high strength and elasticity, excellent resistance to high temperature softening and electrical conductivity, and good bendability.
[0009] A copper alloy strip comprising the following components in mass percentage: Ni: 22-24wt%, Al: 4-5wt%, Sn: 6-7wt%, Ce: 0.05-0.1wt%, impurities <0.15wt%, and the balance Cu;
[0010] The copper alloy strip includes a second strengthening phase Ni 3 Al and Ni 3 Sn, the second strengthening phase Ni 3 Al and Ni 3 The diameter of Sn is within 5nm, and the second reinforcement phase particles per unit area are 6500 / μm 2 above.
[0011] Preferably, the copper alloy strip comprises the following components in percentage by mass: Ni: 23wt%, Al: 4.5wt%, Sn: 6.5wt%, Ce: 0.075wt%, impurities <0.15wt%, and the balance Cu.
[0012] Preferably, the second strengthening phase Ni 3 Al and Ni 3 The diameter of Sn is within 2.5nm, and the second reinforcement phase particles per unit area are 7200 / μm 2 Under this condition, the strength, conductivity and high temperature softening resistance of the copper alloy strip are greatly improved.
[0013] The addition of Al element enables Al and Ni to form a second phase strengthening phase Ni during aging heat treatment.3 Al greatly improves the strength and high temperature softening resistance of the alloy.
[0014] The addition of Sn element enables Sn and Ni to form a second phase strengthening phase Ni during aging heat treatment. 3 Sn greatly improves the strength and high temperature softening resistance of the alloy.
[0015] A trace amount of rare earth element Ce can effectively refine the grain structure of the alloy during casting, playing a role in grain refinement strengthening. Ce can also promote the second phase Ni during aging strengthening. 3 Al and Ni 3 Sn precipitation; at the same time, Ce element is highly active and will react with oxygen first, and the generated oxide inclusions will float up and be discharged from the melt, thus improving the purity of the copper alloy melt and improving the casting performance of the alloy.
[0016] Preferably, the grain size of the copper alloy strip is ≤2 μm.
[0017] The finer the grains, the higher the strength of the material. The grain size of the copper alloy strip of the present invention is controlled within 2 μm, which can greatly improve the strength of the material.
[0018] More preferably, the grain size of the copper alloy strip is ≤1.3 μm.
[0019] Preferably, the copper alloy strip has a tensile strength>1310MPa; a yield strength>1280MPa; and a conductivity≥18%.
[0020] The present invention also provides a method for preparing the copper alloy strip, comprising: batching, smelting, semi-continuous casting, hot rolling, rough rolling, solution annealing, intermediate rolling, aging heat treatment, finished product rolling, and stress relief annealing.
[0021] The hot rolling process is as follows: the ingot heating temperature is 950-1000°C, the holding time is 3-4h, the hot rolling starting temperature is 950-980°C, the hot rolling speed is 200-300m / min, the final rolling temperature is above 800°C, and then online water cooling quenching is performed, and the strip temperature after online water cooling quenching is lower than 180°C;
[0022] The process of the solution annealing is as follows: the annealing temperature is 1050-1100°C, the annealing speed is 100-150m / min, and the protective gas is hydrogen;
[0023] The aging heat treatment process is: firstly heating to 250-300°C and keeping the temperature for 2-3h; then heating to 420-460°C and keeping the temperature for 8-10h.
[0024] The present invention adopts high-temperature rapid hot rolling + final rolling online water-cooling quenching process to prepare copper alloy hot-rolled strip. Since this alloy has a hot brittle zone between 550-750°C, that is, it is easy to crack when hot-processed in this temperature range, in order to ensure the stable hot rolling quality of this alloy, hot rolling must adopt high-temperature rapid rolling to ensure that the final rolling temperature during hot rolling is above 800°C, avoiding the temperature range of the hot rolling brittle zone of this alloy; at the same time, online water cooling is adopted at the final rolling temperature above 800°C during hot rolling, which can effectively ensure that the alloy elements are completely dissolved in the matrix, improve the alloy's subsequent cold processing plasticity, and ensure that the total processing rate during cold processing reaches more than 90%.
[0025] Preferably, the hot rolling processing rate is above 90%, the hot rolling thickness is 15±0.5 mm, and the belt width after widening is 655±5 mm.
[0026] Based on the above hot rolling process, the present invention adopts high temperature rapid solution annealing to fully dissolve the alloy elements in the matrix, thereby improving the solid solubility of the matrix and increasing the precipitation potential energy of the later second phase strengthening phase and the second phase nucleation amount.
[0027] Preferably, the average grain size of the copper alloy strip after solution annealing is controlled within 4 μm, the strip hardness is 120-130 HV, the tensile strength is 420-440 MPa, the elongation is 45-55%, and the conductivity is 9-12% IACS.
[0028] After obtaining the solution annealed copper alloy strip, more preferably, the present invention uses an aging heat treatment process to make the second phase strengthening phase Ni 3 Al and Ni 3 Sn is fully precipitated, ensuring that the conductivity is controlled above 15% IACS, and the second strengthening phase Ni precipitated under this process 3 Al and Ni 3 The diameter of Sn is within 5nm, and the number of second reinforcement phase particles precipitated per unit area is 6500 / μm 2 The above achieves the optimization effect of second phase dispersion strengthening, greatly improving the strength, conductivity and high temperature softening resistance of the material. 3 Al and Ni 3 When the size of Sn is above 10nm, its second phase strengthening effect is greatly reduced, and it is difficult to achieve the optimal strengthening effect.
[0029] In addition, the aging heat treatment process ensures that the finished grain size of the material organization is controlled within 2μm. According to the Hall-Petch formula σ s =σ 0 +Kd -1 / 2 (σ s is the yield strength; σ 0is the yield strength of the single crystal, is a constant; K is the influence coefficient of the grain boundary on the strength, is a constant; d is the average diameter of the grains) It can be seen that the finer the grains within the grain size range, the higher the strength of the material, and this process ensures that the grain size of the finished product is controlled within 2μm, thereby further greatly improving the strength of the material.
[0030] Preferably, the smelting process is as follows: after removing the electrode ear from the electrolytic copper, add it into the smelting furnace to melt, then raise the temperature to 1300-1400°C, add pure nickel, aluminum and tin according to the composition ratio, remove the slag after 30-50 minutes, use a mixed covering agent with a mass ratio of cryolite and sodium carbonate of 1:1 to cover the slag, and the covering thickness is 80-100mm, open the gas diffuser, and introduce 90% high-purity N 2 and 10% high purity CO gas, gas pressure 0.1-0.2MPa, flow rate 10-30L / min. After keeping warm for 1-1.5 hours, add rare earth Ce according to the composition ratio, and keep warm for 10-15 minutes.
[0031] Preferably, the process of semi-continuous casting is as follows: the temperature of the molten copper obtained by smelting is controlled at 1250-1300°C, the cooling water of the crystallizer is turned on, the water pressure is controlled at about 100-150Kpa, the stopper rod is rotated, and the molten copper from the smelting furnace is discharged into the crystallizer. When the height of the molten copper in the crystallizer reaches about two-thirds of the crystallizer, the traction machine is started, and the casting work is started at 30-50mm / min, and the vibration is turned on. The frequency of the vibrator is 50-70 times / min, and the amplitude is 3-6mm. During the casting process, a molten covering agent is added to the crystallizer. The casting speed in the steady-speed casting stage is 50-60mm / min. Red ingot casting is adopted, and the primary cooling water flow rate of the crystallizer is 15-20m 3 / h, water inlet temperature 20-28℃, water outlet temperature controlled at 45-55℃.
[0032] Since this alloy will produce large internal stress during casting and is prone to hot cracks at the casting grain boundaries, the use of red ingot casting and crystallizer cooling can effectively reduce the cooling gradient during casting and effectively solve the generation of hot cracks in the casting of this alloy.
[0033] Preferably, the molten covering agent is cryolite and sodium carbonate in a mass ratio of 1:1. The addition of the molten covering agent follows the principle of "small amounts and multiple times" to prevent bare copper water from being added too little, and to avoid inclusions on the surface of the ingot due to excessive addition of the molten covering agent at a single time. The molten covering agent is evenly sprinkled on the copper liquid surface so that the liquid surface in the crystallizer is covered with a thin molten covering agent.
[0034] Preferably, the rough rolling processing rate is controlled at 90-98%.
[0035] Preferably, the intermediate rolling processing rate is controlled at 80-90%.
[0036] Preferably, the finished product rolling processing rate is controlled at 40-45%.
[0037] Preferably, the stress relief annealing is performed at a temperature of 340-380°C, a speed of 80-100 m / min, and a protective gas of 2-4% H 2 and N 2 of mixed gas.
[0038] The present invention also provides the use of the copper alloy strip in connectors and shrapnel of 5G electrical components. The copper alloy strip of the present invention has ultra-high strength and elasticity, excellent high temperature softening resistance and electrical conductivity, and good bendability, and can be widely used in connectors and shrapnel of 5G electrical components.
[0039] Compared with the prior art, the present invention has at least the following beneficial effects:
[0040] (1) The copper alloy strip of the present invention contains Al and Sn elements. During aging treatment, Ni, Al and Sn can form a second phase strengthening phase Ni. 3 Al and Ni 3 Sn greatly improves the strength and high temperature softening resistance of the alloy.
[0041] (2) The copper alloy strip of the present invention contains a trace amount of rare earth element Ce, which can effectively refine the grain structure of the alloy during casting and play a role in grain refinement strengthening. Ce can also promote the second phase Ni during aging strengthening. 3 Al and Ni 3 Sn precipitates, and Ce element is highly active and will react with oxygen first. The generated oxide inclusions float up and are discharged from the melt, thus improving the purity of the copper alloy melt and the casting performance of the alloy.
[0042] (3) In the semi-continuous casting process of the present invention, the ingot casting adopts the red ingot casting technology, and the crystallizer cooling adopts primary cooling water cooling, which can effectively reduce the cooling gradient during casting and effectively solve the generation of thermal cracks in the casting of this alloy.
[0043] (4) During the hot rolling process of the present invention, high-temperature rapid rolling is adopted to ensure that the final rolling temperature is above 800°C during hot rolling, avoiding the temperature range of the hot rolling brittle zone of this alloy. At the same time, online water cooling is adopted at the final rolling temperature above 800°C during hot rolling, which can effectively ensure that the alloy elements are completely dissolved in the matrix, improve the subsequent cold working plasticity of the alloy, and ensure that the total processing rate during cold working reaches more than 90%.
[0044] (5) The present invention adopts high temperature rapid solution annealing to fully dissolve the alloy elements in the matrix, improve the solid solubility of the matrix, increase the precipitation potential energy of the second phase strengthening phase and the second phase nucleation amount in the later stage. Then, combined with the organization control aging heat treatment, the second phase strengthening phase Ni 3 Al and Ni 3 Sn is fully precipitated, ensuring that the conductivity is controlled above 15% IACS, and the strengthening phase Ni precipitated under this process 3 Al and Ni 3 The diameter of Sn is within 5nm, and the number of second reinforcement phase particles precipitated per unit area is 6500 / μm 2 The above has achieved the optimization effect of second phase dispersion strengthening, greatly improving the strength, conductivity and high temperature softening resistance of the material.
[0045] (6) The copper alloy strip prepared by the method of the present invention has ultra-high strength and elasticity, excellent resistance to high-temperature softening and electrical conductivity and bendability, and its tensile strength is >1310MPa; yield strength is >1280MPa; electrical conductivity is ≥18%, and can be widely used in connectors and shrapnel of 5G electrical components. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with specific embodiments, but is not intended to be limiting of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention may be combined with each other without conflict.
[0047] The specific composition of the copper alloy strip in the embodiment and comparative example of the present invention is shown in Table 1. The key process parameters in the embodiment and comparative example are shown in Table 2.
[0048] Example 1
[0049] (1) Batching and smelting. After removing the pole ear from the electrolytic copper, add it to the smelting furnace and heat it to melt. The melt in the smelting furnace must be tightly covered with dry charcoal. The charcoal used is baked at 200°C for more than 2 hours. The charcoal covering thickness is 135mm. No copper liquid is allowed to be exposed to the air. Then the temperature is raised to 1340°C, and pure nickel, aluminum and tin are added according to the composition ratio. After 38 minutes, the slag is removed and covered with a mixed covering agent of cryolite and sodium carbonate with a mass ratio of 1:1. The covering thickness is 80-100mm. Five gas diffusers are installed at the bottom of the furnace and opened to pass 90% high-purity N 2 and 10% high purity CO gas, gas pressure 0.12MPa, low blowing gas flow rate 18L / min. After 1.45 hours of heat preservation, rare earth Ce is added according to the composition ratio, and after 12 minutes of heat preservation, the temperature of the copper liquid is reduced to 1255℃ to start casting.
[0050] (2) Semi-continuous casting. The temperature of the molten copper is controlled at 1255℃, and then the cooling water of the crystallizer is turned on. At this time, the water pressure is controlled at 130Kpa. Then the stopper rod is rotated to discharge the molten copper from the smelting furnace into the crystallizer. When the height of the molten copper in the crystallizer reaches about two-thirds of the height of the crystallizer, the traction machine is started and the casting work is started at 38mm / min. The vibration is turned on. The frequency of the vibrator is 55 times / min and the amplitude is 5.5mm. During the casting process, a molten covering agent (cryolith and sodium carbonate are in a mass ratio of 1:1) is added to the crystallizer. The molten covering agent is evenly sprinkled on the surface of the molten copper so that the surface of the liquid in the crystallizer is covered with a thin molten covering agent. The addition of the molten covering agent during the entire casting process follows the principle of "small amounts and multiple times" to prevent the bare copper from being added too little, and to avoid the surface inclusion of the ingot caused by adding too much molten covering agent at a single time. The casting speed in the steady-speed casting stage (when the ingot is cast to 400-600mm, the steady-speed casting stage is reached) is 54mm / min, red ingot casting is adopted, and the primary cooling water flow of the crystallizer is 17m 3 / h, water inlet temperature 23℃, water outlet temperature controlled at 49℃, no secondary cooling water cooling after the ingot leaves the crystallizer. The ingot casting specification is 180*630mm*7000mm.
[0051] (3) Hot rolling. High-temperature rapid hot rolling + final rolling online water-cooling quenching process is adopted. The ingot heating temperature is 960℃, the holding time is 3.8h, the hot rolling starting temperature is 960℃, the hot rolling speed is 290m / min, the final rolling temperature is 817℃, and online water-cooling quenching is adopted. After water-cooling quenching, the strip temperature is lower than 180℃. The hot rolling processing rate is more than 90%, the hot rolling thickness is 15±0.5mm, and the width of the strip after widening is 655±5mm.
[0052] (4) Milling: The single-side milling amount is 0.6-0.9mm, and the thickness after milling is 13.5±0.5mm.
[0053] (5) Rough rolling: Rough rolling to 0.8 mm.
[0054] (6) Edge cutting: The single-side cutting is 7-8 mm, and the belt width after cutting is 640 ± 0.5 mm.
[0055] (7) High-temperature rapid solid solution air cushion furnace annealing. A single sheet expansion air cushion furnace is used for annealing, with an annealing temperature of 1090°C, an annealing speed of 140 / min, and a protective gas containing 100% pure H 2 After solution annealing, the average grain size of the strip is controlled within 4μm, the strip hardness is 124HV, the tensile strength is 427MPa, the elongation is 48%, and the conductivity is 11%IACS.
[0056] (8) Intermediate rolling: Intermediate rolling to 0.15 mm.
[0057] (9) Organization control aging heat treatment. Heating to 270℃, keeping temperature for 2.6h, then heating to 450℃, keeping temperature for 9h. After heat treatment, the grain size of the organization is 1.1μm, and the second phase Ni is precipitated. 3 Al and Ni 3 The diameter of Sn strengthening particles is 2nm, and the number of second strengthening phase particles precipitated per unit area of the organization is 8142 / μm 2 above.
[0058] (10) Finished product rolling. The finished product is rolled to 0.085 mm. A 20-roll rolling mill is used for the finished product rolling.
[0059] (11) Online stress relief air cushion furnace annealing. A single sheet expansion air cushion furnace was used for annealing, with an annealing temperature of 370°C, an annealing speed of 90 m / min, and a protective gas containing H 2 The amount is 2.8% and the balance is nitrogen.
[0060] (12) Cleaning. The degreasing agent is sodium hydroxide aqueous solution, pH 8, solution temperature 64 ° C. For pickling, sulfuric acid concentration 120g / l, temperature ≤40 ° C, Cu in acid solution 2+ ≤1.2g / l, clean and dry, oven temperature 69℃.
[0061] (13) Finished products are striped and packaged.
[0062] The properties and microstructure of the copper alloy strip prepared in this example are shown in Table 3.
[0063] Example 2
[0064] (1) Batching and smelting. After removing the pole ear from the electrolytic copper, add it to the smelting furnace and heat it to melt. The melt in the smelting furnace must be tightly covered with dry charcoal. The charcoal used is baked at 200℃ for more than 2h. The charcoal covering thickness is 140mm. No copper liquid is allowed to be exposed to the air. Then the temperature is raised to 1380℃, and pure nickel, aluminum and tin are added according to the composition ratio. After 42 minutes, the slag is removed and covered with a mixed covering agent of cryolite and sodium carbonate with a mass ratio of 1:1. The covering thickness is 80-100mm. Five gas diffusers are installed at the bottom of the furnace and opened to pass 90% high-purity N 2 and 10% high purity CO gas, gas pressure 0.17MPa, low blowing gas flow rate 27L / min. After 1.2 hours of heat preservation, rare earth Ce is added according to the composition ratio, and after 13 minutes of heat preservation, the temperature of the copper liquid is reduced to 1270℃ and casting begins.
[0065] (2) Semi-continuous casting. The temperature of the molten copper is controlled at 1270°C, and then the cooling water of the crystallizer is turned on. At this time, the water pressure is controlled at 125Kpa. Then the stopper rod is rotated to discharge the molten copper from the smelting furnace into the crystallizer. When the height of the molten copper in the crystallizer reaches about two-thirds of the height of the crystallizer, the traction machine is started and the casting work is started at 48mm / min. The vibration is turned on. The frequency of the vibrator is 65 times / min and the amplitude is 3.5mm. During the casting process, a molten covering agent (cryolite and sodium carbonate are in a mass ratio of 1:1) is added to the crystallizer. The molten covering agent is evenly sprinkled on the surface of the molten copper so that the surface of the liquid in the crystallizer is covered with a thin molten covering agent. The addition of the molten covering agent during the entire casting process follows the principle of "small amounts and multiple times" to prevent the bare copper from being added too little, and to avoid the surface inclusion of the ingot caused by adding too much molten covering agent at a single time. The casting speed in the steady-speed casting stage (when the ingot is cast to 400-600mm, the steady-speed casting stage is reached) is 58mm / min, red ingot casting is adopted, and the primary cooling water flow of the crystallizer is 19m 3 / h, water inlet temperature 22℃, water outlet temperature controlled at 50℃, no secondary cooling water cooling after the ingot leaves the crystallizer. The ingot casting specification is 180*630mm*7000mm.
[0066] (3) Hot rolling. High-temperature rapid hot rolling + final rolling online water-cooling quenching process is adopted. The ingot heating temperature is 990℃, the holding time is 3.3h, the hot rolling starting temperature is 965℃, the hot rolling speed is 288m / min, the final rolling temperature is 821℃, and online water-cooling quenching is adopted. After water-cooling quenching, the strip temperature is lower than 180℃. The hot rolling processing rate is more than 90%, the hot rolling thickness is 15±0.5mm, and the width of the strip after widening is 655±5mm.
[0067] (4) Milling: The single-side milling amount is 0.6-0.9mm, and the thickness after milling is 13.5±0.5mm.
[0068] (5) Rough rolling: Rough rolling to 0.78 mm.
[0069] (6) Edge cutting: The single-side cutting is 7-8 mm, and the belt width after cutting is 640 ± 0.5 mm.
[0070] (7) High-temperature rapid solid solution air cushion furnace annealing. A single sheet expansion air cushion furnace is used for annealing, with an annealing temperature of 1055°C, an annealing speed of 125 m / min, and a protective gas containing 100% pure H 2 After solution annealing, the average grain size of the strip is controlled within 4μm, the strip hardness is 125HV, the tensile strength is 431MPa, the elongation is 49%, and the conductivity is 11.5%IACS.
[0071] (8) Intermediate rolling: Intermediate rolling to 0.13 mm.
[0072] (9) Structure control aging heat treatment. Heating to 280℃, keeping temperature for 2.2h, then heating to 425℃, keeping temperature for 10h. After heat treatment, the grain size of the structure is 1.3μm, and the second phase Ni is precipitated. 3 Al and Ni 3 The diameter of Sn strengthening particles is 2.3nm, and the number of second strengthening phase particles precipitated per unit area of the organization is 7288 / μm 2 above.
[0073] (10) Finished product rolling. The finished product is rolled to 0.075 mm, and a 20-roll rolling mill is used for the rolling of the finished product.
[0074] (11) Online stress relief air cushion furnace annealing. A single sheet expansion air cushion furnace was used for annealing, with an annealing temperature of 365°C, an annealing speed of 92 m / min, and a protective gas containing H 2 The amount is 2.4% and the balance is nitrogen.
[0075] (12) Cleaning. The degreasing agent is sodium hydroxide aqueous solution, pH 7.5, solution temperature 62°C. For pickling, sulfuric acid concentration 110g / l, temperature ≤40°C, Cu in acid solution 2+ ≤1.2g / l, clean and dry, oven temperature 66℃.
[0076] (13) Finished products are striped and packaged.
[0077] The properties and microstructure of the copper alloy strip prepared in this example are shown in Table 3.
[0078] Example 3
[0079] (1) Batching and smelting. After removing the pole ear from the electrolytic copper, add it to the smelting furnace and heat it to melt. The melt in the smelting furnace must be tightly covered with dry charcoal. The charcoal used is baked at 200℃ for more than 2h. The charcoal covering thickness is 110mm. No copper liquid is allowed to be exposed to the air. Then the temperature is raised to 1320℃, and pure nickel, aluminum and tin are added according to the composition ratio. After 35 minutes, the slag is removed and covered with a mixed covering agent of cryolite and sodium carbonate with a mass ratio of 1:1. The covering thickness is 80-100mm. Five gas diffusers are installed at the bottom of the furnace and opened to pass 90% high-purity N 2 and 10% high purity CO gas, gas pressure 0.16MPa, low blowing gas flow rate 16L / min. After 1.4 hours of heat preservation, rare earth Ce is added according to the composition ratio, and after 11 minutes of heat preservation, the temperature of the copper liquid is reduced to 1260℃ to start casting.
[0080] (2) Semi-continuous casting. The temperature of the copper liquid is controlled at 1260℃, and then the cooling water of the crystallizer is turned on. At this time, the water pressure should be controlled at about 115Kpa. Then the stopper rod is rotated to discharge the copper liquid from the smelting furnace into the crystallizer. When the height of the copper liquid in the crystallizer reaches about two-thirds of the crystallizer, the traction machine is started and the casting work is started at 35mm / min. The vibration is turned on. The frequency of the vibrator is 67 times / min and the amplitude is 4mm. During the casting process, a molten covering agent (cryolite and sodium carbonate are in a mass ratio of 1:1) is added to the crystallizer. The molten covering agent is evenly sprinkled on the surface of the copper liquid so that the liquid surface in the crystallizer is covered with a thin molten covering agent. The addition of the molten covering agent during the entire casting process follows the principle of "small amounts and multiple times" to prevent the copper liquid from being exposed due to the addition of too little, and to avoid the surface inclusion of the ingot caused by the addition of too much molten covering agent at a single time. The casting speed in the steady-speed casting stage (when the ingot is cast to 400-600mm, the steady-speed casting stage is reached) is 56mm / min, red ingot casting is adopted, and the primary cooling water flow of the crystallizer is 16m 3 / h, water inlet temperature 27℃, water outlet temperature controlled at 48℃, no secondary cooling water cooling after the ingot leaves the crystallizer. The ingot casting specification is 180*630mm*7000mm.
[0081] (3) Hot rolling. High-temperature rapid hot rolling + final rolling online water-cooling quenching process is adopted. The ingot heating temperature is 985℃, the holding time is 3.7h, the hot rolling starting temperature is 970℃, the hot rolling speed is 260m / min, the final rolling temperature is 815℃, and online water-cooling quenching is adopted. After water-cooling quenching, the strip temperature is lower than 180℃. The hot rolling processing rate is more than 90%, the hot rolling thickness is 15±0.5mm, and the width of the strip after widening is 655±5mm.
[0082] (4) Milling: The single-side milling amount is 0.6-0.9mm, and the thickness after milling is 13.5±0.5mm.
[0083] (5) Rough rolling: Rough rolling to 0.75 mm.
[0084] (6) Edge cutting: The single-side cutting is 7-8 mm, and the belt width after cutting is 640 ± 0.5 mm.
[0085] (7) High-temperature rapid solid solution air cushion furnace annealing. A single sheet expansion air cushion furnace is used for annealing, with an annealing temperature of 1065°C, an annealing speed of 130 m / min, and a protective gas containing 100% pure H 2 After solution annealing, the average grain size of the strip is controlled within 4μm, the strip hardness is 122HV, the tensile strength is 426MPa, the elongation is 50%, and the conductivity is 11%IACS.
[0086] (8) Intermediate rolling: Intermediate rolling to 0.12 mm.
[0087] (9) Microstructure control aging heat treatment. Heated to 264℃, kept at this temperature for 2.5h. Then heated to 438℃ and kept at this temperature for 9.4h. After heat treatment, the microstructure grain size was 1.2μm, and the second phase Ni was precipitated. 3 Al and Ni 3 The diameter of Sn strengthening particles is 2.2nm, and the number of second strengthening phase particles precipitated per unit area of the organization is 7549 / μm 2 above.
[0088] (10) Finished product rolling: The finished product is rolled to 0.07 mm.
[0089] (11) Online stress relief air cushion furnace annealing. A single sheet expansion air cushion furnace was used for annealing, with an annealing temperature of 365°C, an annealing speed of 95 m / min, and a protective gas containing H 2 The amount is 3.1% and the balance is nitrogen.
[0090] (12) Cleaning. The degreasing agent is sodium hydroxide aqueous solution, the pH range is 7-9, and the solution temperature is 65°C. For pickling, the sulfuric acid concentration is 120g / l, the temperature is ≤40°C, and the Cu content in the acid is 2+ ≤1.2g / l, clean and dry, oven temperature 68℃.
[0091] (13) Finished products are striped and packaged.
[0092] The properties and microstructure of the copper alloy strip prepared in this example are shown in Table 3.
[0093] Example 4
[0094] (1) Batching and smelting. After removing the pole ear from the electrolytic copper, add it to the smelting furnace and heat it to melt. The melt in the smelting furnace must be tightly covered with dry charcoal. The charcoal used is baked at 200℃ for more than 2h. The charcoal covering thickness is 120mm. No copper liquid is allowed to be exposed to the air. Then the temperature is raised to 1380℃, and pure nickel, aluminum and tin are added according to the composition ratio. After 39 minutes, the slag is removed and covered with a mixed covering agent of cryolite and sodium carbonate with a mass ratio of 1:1. The covering thickness is 80-100mm. Five gas diffusers are installed at the bottom of the furnace and opened to pass 90% high-purity N 2 and 10% high purity CO gas, gas pressure 0.17MPa, low blowing gas flow rate 22L / min. After 1.25 hours of heat preservation, rare earth Ce is added according to the composition ratio, and after 13 minutes of heat preservation, the temperature of the copper liquid is reduced to 1295℃ and casting begins.
[0095] (2) Semi-continuous casting. The temperature of the copper liquid is controlled at 1295℃, and then the cooling water of the crystallizer is turned on. At this time, the water pressure should be controlled at about 145Kpa. Then the stopper rod is rotated to discharge the copper liquid from the smelting furnace into the crystallizer. When the height of the copper liquid in the crystallizer reaches about two-thirds of the crystallizer, the traction machine is started and the casting work is started at 44mm / min. The vibration is turned on. The frequency of the vibrator is 58 times / min and the amplitude is 3.8mm. During the casting process, a molten covering agent (cryolith and sodium carbonate are in a mass ratio of 1:1) is added to the crystallizer. The molten covering agent is evenly sprinkled on the surface of the copper liquid so that the liquid surface in the crystallizer is covered with a thin molten covering agent. The addition of the molten covering agent during the entire casting process follows the principle of "small amounts and multiple times" to prevent the copper liquid from being exposed due to the addition of too little, and to avoid the surface inclusion of the ingot caused by the addition of too much molten covering agent at a single time. The casting speed in the steady-speed casting stage (when the ingot is cast to 400-600mm, the steady-speed casting stage is reached) is 54mm / min, red ingot casting is adopted, and the primary cooling water flow of the crystallizer is 16m 3 / h, water inlet temperature 24℃, water outlet temperature controlled at 48℃, no secondary cooling water cooling after the ingot leaves the crystallizer. The ingot casting specification is 180*630mm*7000mm.
[0096] (3) Hot rolling. High-temperature rapid hot rolling + final rolling online water-cooling quenching process is adopted. The ingot heating temperature is 985℃, the holding time is 3.4h, the hot rolling starting temperature is 978℃, the hot rolling speed is 278m / min, the final rolling temperature is 819℃, and online water-cooling quenching is adopted. After water-cooling quenching, the strip temperature is lower than 180℃. The hot rolling processing rate is more than 90%, the hot rolling thickness is 15±0.5mm, and the width of the strip after widening is 655±5mm.
[0097] (4) Milling: The single-side milling amount is 0.6-0.9mm, and the thickness after milling is 13.5±0.5mm.
[0098] (5) Rough rolling: Rough rolling to 0.7 mm.
[0099] (6) Edge cutting: The single-side cutting is 7-8 mm, and the belt width after cutting is 640 ± 0.5 mm.
[0100] (7) High-temperature rapid solid solution air cushion furnace annealing. A single sheet expansion air cushion furnace is used for annealing, with an annealing temperature of 1050°C, an annealing speed of 135 m / min, and a protective gas containing 100% pure H 2 After solution annealing, the average grain size of the strip is controlled within 4μm, the strip hardness is 128HV, the tensile strength is 434MPa, the elongation is 51%, and the conductivity is 9.5%IACS.
[0101] (8) Intermediate rolling: Intermediate rolling to 0.115 mm.
[0102] (9) Microstructure control aging heat treatment. Heat to 260℃ and keep it for 2.8h. Then heat to 430℃ and keep it for 9.5h. After heat treatment, the grain size of the microstructure is 0.9μm, and the second phase Ni is precipitated. 3 Al and Ni 3 The diameter of Sn strengthening particles is 1.8nm, and the number of second strengthening phase particles precipitated per unit area of the organization is 8964 / μm 2 above.
[0103] (10) Finished product rolling. The finished product is rolled to 0.065 mm, and a 20-roll rolling mill is used for the rolling of the finished product.
[0104] (11) Online stress relief air cushion furnace annealing. A single sheet expansion air cushion furnace was used for annealing, with an annealing temperature of 345°C, an annealing speed of 88 m / min, and a protective gas containing H 2 The amount is 2.2% and the balance is nitrogen.
[0105] (12) Cleaning. The degreasing agent is sodium hydroxide aqueous solution, the pH range is 7.9, and the solution temperature is 63°C. For pickling, the sulfuric acid concentration is 126g / l, the temperature is ≤40°C, the Cu2+ in the acid solution is ≤1.2g / l, and the cleaning and drying oven temperature is 69°C.
[0106] (13) Finished products are striped and packaged.
[0107] The properties and microstructure of the copper alloy strip prepared in this example are shown in Table 3.
[0108] Comparative Example 1
[0109] The difference between Comparative Example 1 and Example 4 is that no Al element is added to the alloy elements.
[0110] The properties and microstructure of the copper alloy strip prepared in this comparative example are shown in Table 3.
[0111] Comparative Example 2
[0112] The difference between Comparative Example 2 and Example 4 is that the annealing temperature during high-temperature rapid air cushion furnace annealing is 750°C.
[0113] The properties and microstructure of the copper alloy strip prepared in this comparative example are shown in Table 3.
[0114] Comparative Example 3
[0115] The difference between Comparative Example 3 and Example 4 is that: the structure-controlled aging heat treatment is heated to 260° C. and kept at this temperature for 2.2 hours, and then heated to 520° C. and kept at this temperature for 8 hours.
[0116] The properties and microstructure of the copper alloy strip prepared in this comparative example are shown in Table 3.
[0117] Table 1 Composition ratio of copper alloy strips of the embodiments of the present invention and the comparative examples (wt%)
[0118] serial number Ni Al Sn Ce Cu Example 1 22.6 4.25 6.3 0.065 margin Example 2 22.8 4.64 6.7 0.07 margin Example 3 23.5 4.82 6.91 0.089 margin Example 4 23 4.5 6.5 0.075 margin Comparative Example 1 23 — 6.5 0.075 margin Comparative Example 2 23 4.5 6.5 0.075 margin Comparative Example 3 23 4.5 6.5 0.075 margin
[0119] The copper alloy strips obtained in the examples and comparative examples were subjected to the following tests, and the specific results are shown in Table 3.
[0120] Mechanical properties testing: The room temperature tensile test is carried out on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2010 Tensile test of metallic materials Part 1: Room temperature test method, using a 20mm wide headed specimen and a tensile speed of 5mm / min.
[0121] The conductivity test is in accordance with GB / T 3048.2-2007 Electrical properties test methods for wires and cables Part 2: Resistivity test of metallic materials and is expressed in %IACS.
[0122] The grain size test of metallographic structure is carried out according to the interception method in GB / T 6394-2007 Determination of average grain size of metals, and the grain size in the photo collected by 1000 times metallographic microscope is tested. The sample width is 10mm and the length is 10mm.
[0123] Table 2 Key process parameter control of the embodiments of the present invention and the comparative examples
[0124]
[0125] Table 3 Structure and properties of copper alloy strips of the embodiments of the present invention and the comparative examples
[0126]
Claims
1. A copper alloy strip, characterized in that: It is composed of the following components in mass percentage: Ni: 22-24 wt%, Al: 4-5 wt%, Sn: 6-7 wt%, Ce: 0.05-0.1 wt%, impurities <0.15wt%, and the balance is Cu; The copper alloy strip comprises a second strengthening phase of Ni3Al and Ni3Sn, wherein the diameter of the second strengthening phase of Ni3Al and Ni3Sn is within 5nm, and the second strengthening phase particles per unit area are 6500 / μm 2 above.
2. The copper alloy strip according to claim 1, characterized in that: The diameter of the second strengthening phase Ni3Al and Ni3Sn is within 2.5nm, and the second strengthening phase particles per unit area are 7200 / μm 2 above.
3. The copper alloy strip according to claim 1, characterized in that: The grain size of the copper alloy strip is ≤2 μm.
4. The copper alloy strip according to claim 1, characterized in that: The copper alloy strip has a tensile strength of >1310MPa, a yield strength of >1280MPa, and a conductivity of ≥18%.
5. The method for preparing a copper alloy strip according to any one of claims 1 to 4, comprising: Batching, smelting, semi-continuous casting, hot rolling, rough rolling, solution annealing, intermediate rolling, aging heat treatment, finished product rolling, stress relief annealing, characterized in that: The hot rolling process is as follows: the ingot heating temperature is 950-1000°C, the holding time is 3-4h, the hot rolling starting temperature is 950-980°C, the hot rolling speed is 200-300m / min, the final rolling temperature is above 800°C, and then online water cooling quenching is performed, and the strip temperature after online water cooling quenching is lower than 180°C; The process of the solution annealing is as follows: the annealing temperature is 1050-1100°C, the annealing speed is 100-150m / min, and the protective gas is hydrogen; The aging heat treatment process is: firstly heating to 250-300°C and keeping the temperature for 2-3h; then heating to 420-460°C and keeping the temperature for 8-10h.
6. The preparation method according to claim 5, characterized in that: The hot rolling processing rate is above 90%, the hot rolling thickness is 15±0.5mm, and the belt width after widening is 655±5mm.
7. The preparation method according to claim 5, characterized in that: The average grain size of the copper alloy strip after solution annealing is controlled within 4 μm, the strip hardness is 120-130 HV, the tensile strength is 420-440 MPa, the elongation is 45-55%, and the conductivity is 9-12% IACS.
8. The preparation method according to claim 5, characterized in that: The annealing temperature of the stress relief annealing is 340-380°C, the speed is 80-100m / min, and the protective gas is a mixture of 2-4% H2 and N2.
9. The preparation method according to claim 5, characterized in that: The rough rolling processing rate is controlled at 90-98%; the intermediate rolling processing rate is controlled at 80-90%; and the finished product rolling processing rate is controlled at 40-45%.
10. Use of the copper alloy strip according to any one of claims 1 to 4 in connectors and springs of 5G electrical components.
Citation Information
Patent Citations
Copper alloy strip and preparation method and application thereof
CN116136005A
Copper alloy and preparation method thereof
CN114672693A
High-strength conductive elastic copper alloy and preparation method thereof
CN115094266A
